Genetically modifying livestock for improved welfare: A path forward - Shriver, A; McConnachie, E (Springer Verlag, 2018)
In recent years, humans’ ability to selectively modify genes has increased dramatically as a result of the development of new, more efficient, and easier genetic modification technology. In this paper, we argue in favor of using this technology to improve the welfare of agricultural animals. We first argue that using animals genetically modified for improved welfare is preferable to the current status quo. Nevertheless, the strongest argument against pursuing gene editing for welfare is that there are alternative approaches to addressing some of the challenges of modern agriculture that may offer ethical advantages over genetic modification; namely, a dramatic shift towards plant-based diets or the development of in vitro meat. Nevertheless, we provide reasons for thinking that despite these possible comparative disadvantages there are important reasons for continuing the pursuit of welfare improvements via genetic modification.